Peran Lansekap Dalam Kinerja Infrastruktur Perkotaan Studi kasus: Surabaya dan Malang, Indonesia - Ramdlani, Subhan; Wulandari, Lisa Dwi; Adhitama, M. Satya; Turningtyas, Turningtyas (RUAS, 2013)
Transportation has been recognized as one of the indicators instrumental in the development of the city. However, the development of transport seems to have the impact on the environment in the spatial and temporal large of coverage (Rini , 2005) . The impact of high transport movements will contribute to vehicle air pollution, thermal energy (temperature) and noise (Soedomo, 1999). In Indonesia, stations, airports, public transport infrastructure and other terminals, has a noise level of up to 70 dB (SK.MLH 24/11, 1996). Landscape Infrastructure is one of the strategies new urban designs to extend the performance parameters of a landscape that is designed for high-performance multi - system function, including those originally thought to be derived from the traditional system infrastructure. Thinking in terms of Landscape Infrastructure adds several advantages to traditional infrastructure : the beauty of the city and re-vegetation/forestation, water and energy conservation; restoration of natural systems, storm water management, agriculture, energy, expansion of wildlife habitat; favoured the use of pedestrians , and expanded parks and open space areas built ignored by the existing urban infrastructure (Aquino, 2011) . This paper will discuss and how to optimize the design of the infrastructure landscape for urban transport infrastructure to minimize air pollution, noise and energy conservation, in terms of transport infrastructure in Malang and Surabaya, Indonesia